THE INFLUENCE OF MOTIVATION, LEADERSHIP, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT SABANG MERAUKE TRADING (SMT) - Yustinus Eri Prastiantoko; Susanto Susanto; Setyo Arief Arachman (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
This study aims to describe the problems that exist in PT Sabang Merauke Trading as an importer of products where the development of the business sector as an importer is an opportunity for small companies for sub-sectoral jobs. Take advantage of opportunities to reach consumers, creating competition between similar technology service companies. This also makes every company have to innovate creative marketing strategies in selling the services offered to the target audience. PT SABANG MERAUKE TRADING (SMT), is a service company, which was founded in 2017 and is engaged in importer services. Constraints that often occur are when the project work schedule is under these circumstances, the need for leadership directions, company motivation and good work discipline between field of work at PT SABANG MERAUKE TRADING (SMT) Indonesia so that employee performance can be followed up as soon as possible so as not to cause disappointment from consumers. The results of the study stated that work motivation and discipline have an influence on employee performance, while leadership has no influence on employee performance.